2003
DOI: 10.1105/tpc.009670
|View full text |Cite
|
Sign up to set email alerts
|

Members of the Arabidopsis Dynamin-Like Gene Family, ADL1, Are Essential for Plant Cytokinesis and Polarized Cell Growth[W]

Abstract: Polarized membrane trafficking during plant cytokinesis and cell expansion are critical for plant morphogenesis, yet very little is known about the molecular mechanisms that guide this process. Dynamin and dynamin-related proteins are large GTP binding proteins that are involved in membrane trafficking. Here, we show that two functionally redundant members of the Arabidopsis dynamin-related protein family, ADL1A and ADL1E, are essential for polar cell expansion and cell plate biogenesis. adl1A-2 adl1E-1 double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
221
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(237 citation statements)
references
References 71 publications
13
221
3
Order By: Relevance
“…Furthermore, we analysed the behaviour of two dynamin-related proteins, DRP1A and DRP1C, which are involved in the clathrinmediated endocytosis in plants [42][43][44] . As previously reported, both DRP1A and DRP1C localize to the cell plate and the plasma membrane of expanding and fully expanded interphase cells 44,45 . Notably, we found that both DRP1A and DRP1C exhibit a similar polarized pattern to that of CHER1 in SE cells (Fig.…”
Section: Resultsmentioning
confidence: 50%
“…Furthermore, we analysed the behaviour of two dynamin-related proteins, DRP1A and DRP1C, which are involved in the clathrinmediated endocytosis in plants [42][43][44] . As previously reported, both DRP1A and DRP1C localize to the cell plate and the plasma membrane of expanding and fully expanded interphase cells 44,45 . Notably, we found that both DRP1A and DRP1C exhibit a similar polarized pattern to that of CHER1 in SE cells (Fig.…”
Section: Resultsmentioning
confidence: 50%
“…Stubs at either side of the cell can be caused by defective maturation and tearing of the plate in mutants impeded in cell wall formation (Nickle and Meinke, 1998;Fagard et al, 2000;Schrick et al, 2000Schrick et al, , 2004Zuo et al, 2000;Lane et al, 2001;Lukowitz et al, 2001;Pagant et al, 2002). However, this does not explain the presence of stubs in mutants affected in early cell plate vesicle-trafficking events, like KN and KEULE (Lauber et al, 1997;Waizenegger et al, 2000), stomatal cytokinesis defective1 (Falbel et al, 2003), the dynamin drp1A drp1E double mutant (Kang et al, 2003a), the double gn/gnl1 mutant mimicked by BFA treatment of gnl1 (Reichardt et al, 2007), and dominant inhibitory mutants of RAB-A2 (Chow et al, 2008). As the inhibition of both GN and GNL1 impairs ER-to-Golgi vesicle trafficking and traps KN in the ER, the cell wall stubs have to be generated by a KN-independent pathway (Lauber et al, 1997;Jurgens, 2005a).…”
Section: Trafficking During Cell Plate Fusion To the Parental Pmmentioning
confidence: 90%
“…Interestingly, in BY-2 cells, clathrin as well as several DRP1 family proteins accumulate at the periphery of the cell plate, where vesicle fusion takes place (Hong et al, 2003;Kang et al, 2003aKang et al, , 2003bTahara et al, 2007), which could reflect membrane recycling.…”
Section: Vesicle Trafficking Involved In Cell Plate Maturationmentioning
confidence: 99%
“…One possible reason for its visibility is that this machine consists of at least three layers: an innermost ring comprising FtsZ, followed by the plastid dividing ring that is visible by negative staining but is of unknown composition 102 , and an outermost ring on the outside of the organelle that contains a dynamin-like protein (DRP) 103,104 . Dynamins are eukaryotic GTPases that assemble on membranes and mediate membrane fission 97 ; dynamin also has a role in cytokinesis of animal and plant cells 105,106 . DRPs have no structural homology with FtsZ, and obvious homologues are absent from prokaryotes.…”
Section: Ftsz and Organelle Division Plastid Divisionmentioning
confidence: 99%